2016
DOI: 10.1177/1079063216630749
|View full text |Cite
|
Sign up to set email alerts
|

Preventative Services for Sexual Offenders

Abstract: The role of primary prevention of sexual offences is an understudied area. The current study examined a sample ( N = 100) of men charged or convicted of a sexual offence to determine their interest in interventions that could be offered prior to offending, reasons for not seeking out interventions in the past, and demographic information including onset of deviant sexual fantasy and interests. The majority indicated that preventative interventions, including individual and group treatment, would have been bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…McCartan et al (2018) reported that some individuals were hesitant to search for available services online or disclose their sexual issues to a healthcare provider in order to get a treatment referral, as they were uncertain of the legal consequences of these actions. These findings are in line with another recent study, which found that barriers to treatment included participants' concerns they would be arrested or labeled as a sexual deviant, as well as concerns about privacy and anonymity (Piché et al, 2018). These concerns may be especially prominent for individuals who are sexually attracted to children but have not acted on this sexual interest.…”
Section: Barriers To Primary and Secondary Preventionsupporting
confidence: 89%
See 3 more Smart Citations
“…McCartan et al (2018) reported that some individuals were hesitant to search for available services online or disclose their sexual issues to a healthcare provider in order to get a treatment referral, as they were uncertain of the legal consequences of these actions. These findings are in line with another recent study, which found that barriers to treatment included participants' concerns they would be arrested or labeled as a sexual deviant, as well as concerns about privacy and anonymity (Piché et al, 2018). These concerns may be especially prominent for individuals who are sexually attracted to children but have not acted on this sexual interest.…”
Section: Barriers To Primary and Secondary Preventionsupporting
confidence: 89%
“…For MAP, sexual attraction to children is likely an inherent part of the motivation to engage in CSA, yet research has indicated that other underlying motivators may also contribute to their offending behaviour, including abuse in childhood (Nunes et al, 2013;Sullivan & Sheehan, 2016), cognitive distortions and abuse-supportive attitudes (Helmus et al, 2013), desire for intimacy and emotional gratification (Ward et al, 1993), and the use of maladaptive coping mechanisms that may indirectly lead to sexual offending (Ward et al, 2007). In some cases, MAP spend years successfully resisting their urge to engage in CSA (Piché et al, 2018), until the accumulation of multiple life stressors act as a catalyst for the transition from sexual interest to sexual behaviour (Leclerc et al, 2016). Studies have shown that a number of underlying motivations for engaging in CSA are endorsed by those both with and without a sexual interest in children.…”
Section: Motivations For Child Sexual Abusementioning
confidence: 99%
See 2 more Smart Citations
“…As long as the social consensus remains punitive in nature, these kinds of preventative and rehabilitative schemes are unlikely to be accessible to those who need help, through fear of social and judicial reprisals, and self-stigmatization (Jahnke & Hoyer, 2013;Piché, Mathesius, Lussier, & Schweighofer, 2016).…”
Section: Discussionmentioning
confidence: 99%